2021
DOI: 10.1007/s10055-021-00602-6
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting fashion x-commerce through the empowerment of voice in the fashion virtual reality arena

Abstract: The ongoing development of eXtended Reality (XR) technologies is supporting a rapid increase of their performances along with a progressive decrease of their costs, making them more and more attractive for a large class of consumers. As a result, their widespread use is expected within the next few years. This may foster new opportunities for e-commerce strategies, giving birth to an XR-based commerce (x-commerce) ecosystem. With respect to web and mobile-based shopping experiences, x-commerce could more easil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…82% of regular users use SVAs to search for information (news, weather, recipes and advice), 67% to listen to music or stream movies, 36% to contact customer service and 35% to buy things (e.g., groceries, home care, or clothes) (Hernandez-Ortega and Ferreira, 2021). Overall, these results suggest that SSRs have a bright future and emphasize the necessity of good partnerships between enterprises and fashion retail customers (Morotti et al, 2021).…”
Section: Embedded Ai Smart Speech Recognitionmentioning
confidence: 97%
See 2 more Smart Citations
“…82% of regular users use SVAs to search for information (news, weather, recipes and advice), 67% to listen to music or stream movies, 36% to contact customer service and 35% to buy things (e.g., groceries, home care, or clothes) (Hernandez-Ortega and Ferreira, 2021). Overall, these results suggest that SSRs have a bright future and emphasize the necessity of good partnerships between enterprises and fashion retail customers (Morotti et al, 2021).…”
Section: Embedded Ai Smart Speech Recognitionmentioning
confidence: 97%
“…A few empirical studies confirmed the use of VAs for fashion shopping (e.g. Morotti et al, 2021;Kautish et al, 2023), but these did not discuss the motivations for using VA technology for fashion shopping (Kautish et al, 2023). Therefore, the goal of this study is to close this empirical gap by examining the effect of embedded AI smart speech recognition-specific features on the fashion retail shopping behaviour related to the customer's purchase intention (PI).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome these shortcomings, cuttingedge digital technologies (i.e. 3D human body scanning and virtual reality) have been utilized for reshaping the entire garment customization process in a more sustainable way [13][14][15][16]. One of the most representative technologies is 3D digital simulation, also named virtual fitting, virtual try-on, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Virtual Reality (VR), Augmented Reality (AR), and Mixed Reality (MR) are the major development in the future of human-computer interaction, which are widely used in digital reading, gaming, intelligent driving, smart healthcare, and other fields. Extended Reality (XR) means all virtual technologies generated by computer, in which "X" represents any current or future technological variable [1]. The distinction between VR and AR hardware devices is fading.…”
Section: Introductionmentioning
confidence: 99%